2010
DOI: 10.1021/jm1008264
|View full text |Cite
|
Sign up to set email alerts
|

Side Chain Cyclization Based on Serine Residues: Synthesis, Structure, and Activity of a Novel Cyclic Analogue of the Parathyroid Hormone Fragment 1−11

Abstract: The N-terminal region of the parathyroid hormone (PTH) is sufficient to activate the G-protein-coupled PTH receptor 1 (PTHR1). The shortest PTH analogue displaying nanomolar potency is the undecapeptide H-Aib-Val-Aib-Glu-Ile-Gln-Leu-Nle-His-Gln-Har-NH(2) that contains two helix-stabilizing residues (Aib(1,3)). To increase the helical character and proteolytic stability of this linear peptide, we replaced Gln(6,10) with (a) Lys(6) and Glu(10) to introduce a lactam bridge and (b) Ser(6,10) to form a diester brid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 61 publications
0
18
0
2
Order By: Relevance
“…More precisely, they showed that 3 10 [35,34]. More precisely, the values would be 0.20 < R < 0.40 in the case of 3 10 helix and 0.85 < R < 0.90 in the case of the a-helix [39,40]. The ratio [θ] 223 /[θ] 205 value being of~0.31 in our case, a 3 10 helix for 7 seems likely [16,35,36].…”
Section: Cyclised Peptidesmentioning
confidence: 55%
“…More precisely, they showed that 3 10 [35,34]. More precisely, the values would be 0.20 < R < 0.40 in the case of 3 10 helix and 0.85 < R < 0.90 in the case of the a-helix [39,40]. The ratio [θ] 223 /[θ] 205 value being of~0.31 in our case, a 3 10 helix for 7 seems likely [16,35,36].…”
Section: Cyclised Peptidesmentioning
confidence: 55%
“…The diester-and lactam-bridged macrocyclic peptides 3 and 4 further exemplified achievements in harnessing the helical sequences of G-protein coupled receptor agonists corresponding to glucagon-like peptide-1 and parathyroid hormone. 120,121 Likewise, a lactam-bridged peptide (not shown) was found to demonstrate a propensity for adopting an a-helical structure within a BH3 sequence. 122 The most robust methodologies used to generate macrocylic a-helical peptide strategies [19][20][21][22][23][24] include ring-closing metathesis and azidealkyne cycloaddition, and such have established a growing armamentarium of stapled peptides 5-26 (Figures 9.3-9.8).…”
Section: Structural Diversity and Chemistry Of Macrocyclicmentioning
confidence: 94%
“…Historically, numerous strategies have emerged to create novel synthetic a-helical secondary structure proteomimetics. [19][20][21][22][23][24]43,44,47,48,56,57,64,[118][119][120][121][122] Albeit not detailed in this focused review, such strategies have included N-terminal helicalinducing capping moieties, [123][124][125] non-peptide foldamers/oligomers 126,127 and small-molecule mimetics. [128][129][130][131][132][133][134][135][136] Unquestionably, the most rewarding strategy has been proven to be the synthesis of macrocyclic a-helical peptides utilizing a variety of linkers, including disulfide, 118 Pioneering studies on macrocylic a-helical peptides first demonstrated 118,119 the effective use of disulfide-bridged and bis-lactam-bridged macrocyclic peptides 1 and 2 ( Figure 9.2), respectively, and focused on model systems wherein a-helicity properties were confirmed by circular dichroism and/or NMR spectroscopy.…”
Section: Structural Diversity and Chemistry Of Macrocyclicmentioning
confidence: 99%
“…Starting from a helical peptide segment derived from the sequence of Tiam1 that interacts with Rac1, we designed a small peptide library. In particular, the insertion of an unnatural alpha, alpha disubstituted amino acid, that is norbornane amino acid, and the side chain stapling have been evaluated as strategies to obtain engineered peptides. Indeed, these approaches might lead to peptides that are stable to metabolism, inherently stable to proteases and peptidases, and can fold into well‐ordered secondary structures …”
Section: Introductionmentioning
confidence: 99%